Implementation of a heterodyne demodulator for blood flow sense discrimination in a bi-directional ultrasonic Doppler detector - García, F.; Solano, J; Fuentes, M.; Rubio, E. (Revista Mexicana de Ingenieria Biomedica, 2015)
Doppler ultrasound systems have been widely used in medical diagnosis, in the study of blood flow, in particular, in the diagnosis of vascular disorders. This is mainly due to its non-invasive method and its relatively low cost. An important feature of the ultrasonic Doppler system is the capability to detect the signal associated with the blood flow and discriminate its direction. The Doppler ultrasound signal contains information associated with the velocity of the blood components, and its frequency spectrum represents the velocity profile of blood flow, which may be direct or reverse. Typically Doppler ultrasound systems which detect the sense of the direction of blood flow signal, are based on methods of homodyne demodulation in quadrature. However the signals produced by these detectors require an additional separation process. This paper addresses the implementation of a heterodyne demodulator as a part of a Doppler ultrasound detector for measuring bi-directional blood flow. We describe the detection process of the Doppler ultrasound blood flow signal and its representation in the form of a two-dimensional spectrogram. Doppler blood flow sensing devices and their classification according to their operation mode and type of demodulation are also described. Finally, functionality tests are presented and results are analyzed.